Molecular epidemiology and characterization of antimicrobial-resistant Staphylococcus haemolyticus strains isolated from dairy cattle milk in Northwest, China - Shoaib, Muhammad; Xu, Jie; Meng, Xiaoqin; Wu, Zhongyong; Hou, Xiao; He, Zhuolin; Shang, Ruofeng; Zhang, Hongjuan; Pu, Wanxia (Frontiers in Cellular and Infection Microbiology, 2023)
Non-aureus staphylococcus (NAS) species are currently the most commonly identified agent’s causing sub-clinical infections of the udder and deemed as an opportunistic agent in clinical mastitis in dairy cattle. More than 10 NAS species have been identified and studied but little is known about S. haemolyticus associated with dairy mastitis and clinical infections in humans. The present study focused on molecular epidemiology and genotypic characterization of S. haemolyticus isolated from dairy cattle milk in Northwest, China. In this study, a total of 356 milk samples were collected from large dairy farms in 3 provinces in Northwest, China. In total, 39/356 (11.0%) were identified as positive for S. haemolyticus. The overall prevalence of other staphylococcus species was noted to be 39.6% (141/356), while the species distribution was as follows: S. aureus 14.9%, S. sciuri 10.4%, S. saprophyticus 7.6%, S. chromogenes 4.2%, S. simulans 1.4%, and S. epidermidis 1.1%. The AST of 39 S. haemolyticus strains exhibited higher resistance to erythromycin (92.3%) followed by trimethoprim-sulfamethoxazole (51.3%), ciprofloxacin (43.6%), florfenicol (30.8%), cefoxitin (28.2%), and gentamicin (23.1%). All of the S. haemolyticus strains were susceptible to tetracycline, vancomycin, and linezolid. The overall percentage of multi-drug resistant (MDR) S. haemolyticus strains was noted 46.15% (18/39). Among ARGs, mphC was identified as predominant (82.05%), followed by ermB (33.33%), floR (30.77%), gyrA (30.77%), sul1 (28.21%), ermA (23.08%), aadD (12.82%), grlA (12.82%), aacA-aphD (10.26%), sul2 (10.26%), dfrA (7.69%), and dfrG (5.13%). The PFGE categorized 39 S. haemolyticus strains into A-H phylogenetic groups while the MLST categorized strains into 8 STs with ST8 being the most predominant while other STs identified were ST3, ST11, ST22, ST32, ST19, ST16, and ST7. These results revealed epidemiology and phenotypic along with the genotypic patterns of AMR, phylogenetic grouping, and sequence types of S. haemolyticus strains from dairy origin. These findings provided new insights in our understanding of the epidemiology and genetic characteristics of S. haemolyticus in dairy farms to inform interventions limiting the spread of AMR in dairy production.